2020
DOI: 10.1155/2020/8518396
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality of Hospitalized Patients, Contributing Factors, and Prevalence of Associated Disorders

Abstract: Background. Data in the literature has shown poor sleep quality to be frequently observed in hospitalized patients and known to be associated with poor treatment outcome. Many factors may impact poor sleep quality, and there is currently limited available data. We aim to determine the prevalence of poor sleep quality and associated factors in patients admitted to internal medicine wards as well as the change of sleep quality over time after admission. Methods. An analytic observational study was conducted at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
3
27
1
3
Order By: Relevance
“…The financial gain from SDD after AF ablation has not been previously explored. From the patient perspective, SDD facilitates better quality of overnight rest at home 16 and the shorter length of stay reduces the risk of hospital acquired infections, which is particularly relevant in the era of the Covid‐19 pandemic 17 . From the hospital perspective, SDD reduces the operating costs associated with extended management of patients deemed appropriate for discharge and allows re‐allocation of healthcare resources, primarily the hospital bed, to other patients in need.…”
Section: Discussionmentioning
confidence: 99%
“…The financial gain from SDD after AF ablation has not been previously explored. From the patient perspective, SDD facilitates better quality of overnight rest at home 16 and the shorter length of stay reduces the risk of hospital acquired infections, which is particularly relevant in the era of the Covid‐19 pandemic 17 . From the hospital perspective, SDD reduces the operating costs associated with extended management of patients deemed appropriate for discharge and allows re‐allocation of healthcare resources, primarily the hospital bed, to other patients in need.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that, prevalence of sleep disturbance among critical ill and hospitalized patients has been shown to be more than (50%), and of the remaining sleep time only 3.0% to 4.0% in REM stage [3]. In another study High prevalence of poor sleep quality in hospitalized patients to be ranging between 43% and 91% [4].…”
Section: Introductionmentioning
confidence: 90%
“…Research demonstrates that poor sleep quality after the first night of hospital admission is high compared to baseline sleep quality at home (50% vs. 18.8%, p < 0.001 in one Thai sample; mean 5.5 versus 7.0 hours, p < 0.0001 in a Canadian sample). 100,101 However, sub-analyses demonstrated that results did not differ by sex. 101 Women are also more likely than men to report post-discharge and post-ICU sleep disturbances.…”
Section: Sex Insomnia and Cvdmentioning
confidence: 82%